Computing well-founded semantics of deductive databases - Nguyen Viet Hai; Phan, Minh Dung; Huynh, Ngoc Phien; Sadananda, Ramakoti; The Australian Government (Bangkok : Asian Institute of Technology, 1990)
In this study we present a bottom-up procedure to compute the well-founded semantics of a datalog program (function free logic program) on a language with infinitely many constants. The distinguished features of our approach are: Our method can be applied to any program: The class of programs for which our method can be applied is neither restricted to the class of stratified nor locally stratified programs as in some other methods. There is also no restriction about the existence of a complete well-founded model and the method can be used to compute the well founded partial model. The underlying language is permitted to have infinitely many constants .
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1990
Keywords: Programming languages (Electronic computers) -- Semantics